Governance and policy in Africa - Abdalla Hamdok (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The recent emphasis on governance in Africa is unique in that it was initiated by donors and not by domestic leaders under pressure from their own constituencies. Thus while many countries have embraced the market economy and liberalized their policies, issues related to political participation, democracy, and institution building have proven harder to tackle. This paper is a review of the good governance debate in Africa. It argues that good governance presupposes the existence of effective domestic institutions. It is only when these are in place and functioning that we shall begin to see a change towards more inclusive policy making.
Keywords: P16; O55; K4; 330; governance; accountability; economic reform; politics; Regierung; Politische Reform; Good Governance; Wirtschaftsreform; Afrika